Coded modulation using superimposed binary codes - Ma, X.; Ping, L. (IEEE transactions on information theory, 2004)
In this correspondence, we investigate in a comprehensive fashion a one-layer coding/shaping scheme resembling a perfectly cooperated multiple-access system. At the transmitter, binary data are encoded by either single-level or multilevel codes. The coded bits are first randomly interleaved and then entered into a signal mapper. At each time, the signal mapper accepts as input multiple binary digits and delivers as output an amplitude signal, where the input are first independently mapped into 2-PAM signals (possibly having different amplitudes) and then superimposed to form the output. The receiver consists of an iterative decoding/demapping algorithm with an entropy-based stopping criterion. In the special cases when all the 2-PAM signals have equal amplitudes, based on an irregular trellis, we propose an optimal soft-input-soft-output (SISO) demapping algorithm with quadratic rather than exponential complexity. In the general cases, when multilevel codes are employed, we propose power-allocation strategies to facilitate the iterative decoding/dempaping algorithm. Using the unequal power-allocations and the Gaussian-approximation-based suboptimal demapping algorithm (with linear complexity), coded modulation with high bandwidth efficiency can be implemented.